Efficiency Enhancement of the Single Line Multi-Stage Gasification of Hungarian Low-Rank Coal: Effects of Gasification Temperature and Steam/Carbon (S/C) Ratio - Mai, Thuan Duc; Koós, Tamás; Sebe, Emese; Siménfalvi, Zoltán; Kállay, András Arnold (Energies (Basel), 2023)
Coal gasification is considered a promising solution for the production of synthetic fuels and eventually as a fuel for combined heat and power systems and heating buildings. There are several factors that affect the gasification efficiency and syngas quality, such as gasification parameters (temperature, pressure, etc.), reactants and their ratio, utilisation of catalysts, and gasifier design. The multi-stage gasifier is known as a promising approach in the enhancement of process efficiency, as well as the syngas quality. In this study, the Hungarian brown coal was gasified in a two-stage gasifier. The pyrolysis stage was kept at 600 °C. The gasification stage was conducted at 700, 800, and 900 °C. The steam per carbon (S/C) ratio was examined at 0.75, 1.00, and 1.25. The positive effects of increasing gasification temperature on char and dry gas yield were obviously shown at all S/C ratios. The increase in the S/C ratio did not show a positive effect at all temperature conditions, especially at 700 and 900 °C. The highest dry syngas yield was 1.14 Nm3/kgcoal obtained at 900 °C and the S/C ratio of 1.25. The increase in the gasification temperature also had a significant impact on the volume fraction of CO and CO2. Meanwhile, the syngas concentration varied slightly when the S/C ratio increased from 0.75 to 1.25. From a chemical utilization point of view, the gasification temperature at 900 °C and the S/C ratio of 1.25 resulted in the most promising H2/CO ratio of 1.99. In addition, the highest carbon conversion and cold gas efficiency were achieved at 900 °C and an S/C ratio of 1.00–1.25, respectively.